The Gut-Muscle Axis in Sarcopenia: A Meta-Analysis of Gut Microbiome Compositional Features and Their Correlation with Muscle Mass, Strength, and Physical Performance in Older Adults - Vyora Ulvyana; Roza Mulyana; Rose Dinda Martini (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Sarcopenia, the age-related decline in muscle mass and function, is a major geriatric syndrome. The gut-muscle axis has emerged as a key area of investigation, yet the association between gut microbiome composition and sarcopenic parameters in humans remains quantified by a collection of studies with varied methodologies. This meta-analysis aimed to synthesize the existing correlational evidence linking gut microbiome features to the core components of sarcopenia in older adults. Methods: We performed a systematic search of PubMed, Scopus, Web of Science, and Embase for observational studies published between January 2015 and July 2025 that assessed gut microbiome composition and sarcopenia metrics in adults aged ≥60. Correlation coefficients (r) were pooled using a random-effects model. We assessed heterogeneity using the I² statistic, conducted pre-specified subgroup and sensitivity analyses, and evaluated study quality with the Newcastle-Ottawa Scale (NOS). Results: Six cross-sectional studies (N=1,189) met the inclusion criteria. The methodological quality was high (median NOS score = 8). The pooled analysis revealed a significant, small positive correlation between gut microbial alpha diversity and muscle strength (handgrip strength) (pooled r = 0.19, 95% CI: 0.11-0.27; I² = 41%). The relative abundance of the genus Faecalibacterium, known for its potential to produce butyrate, was significantly correlated with physical performance (pooled r = 0.24, 95% CI: 0.16-0.32; I² = 28%). A non-significant negative correlation was found between the family Enterobacteriaceae and muscle mass (pooled r = -0.14, 95% CI: -0.29-0.01; I² = 62%). Subgroup analysis suggested this heterogeneity was partly explained by the diagnostic criteria used for sarcopenia. Conclusion: This meta-analysis provides quantitative evidence of a modest but significant association between gut microbiome composition and muscle health in older adults. A microbial profile with higher diversity and greater abundance of putative beneficial taxa is correlated with better muscle function. These associative findings, while limited by the cross-sectional nature of the data and the potential for reverse causality, reinforce the clinical relevance of the gut-muscle axis and underscore the need for longitudinal, multi-omic studies to elucidate mechanisms and test microbiome-targeted therapies.